A New Joint Source-Channel Coding in the Short Blocklength Regime - Wang, Qianfan; Chen, Yanzhi; Liang, Jifan; Wei, Baodian; Mat, Xiao (2023 IEEE Globecom Workshops (GC Wkshps), 2023)
In this paper, we propose a new joint source-channel coding (JSCC) for short blocklength sources. The proposed JSCC scheme is universal in the sense that it does not require the knowledge of source statistics. At the transmitter, the source information is firstly encoded by a two-stage description, referred to as classified enumerative (CE) coding, and then encoded by a matched multiple-rate code. The two-stage CE coding describes a binary sequence by its type class and its rank in the associated type class, which can approach the entropy for biased sources. The multiple-rate Reed-Muller coding transforms the variable-length codeword of the CE coding into a fixed-length transmitted codeword, allocating lower energy to lower-rate component codes. At the receiver, the source can be recovered by a CRC-aided parallel decoding, exhibiting a low decoding delay. To predict the performance of the proposed JSCC scheme, we present an estimated bound based on the performance of each type of information. Simulation results show that the performance matches well with the presented bound, validating our analysis. They also show that the proposed JSCC scheme can approach the JSCC bounds (exhibiting a gap of less than 0.5 dB) and can outperform the double polar JSCC scheme (exhibiting a coding gain of up to 0.3 dB).